Technocratic belief or civil society: reflections on the typological concepts of sociology - A. V. Shcherbina (Дискурс, 2019)
Introduction. Digitalization is widely discussed as a global trend of modern times in a media agenda and experts debates. Digital technologies, such as communication, computing and management technologies, have already changed the modes of interaction of one individual with another individual, family, and inner circle, as well as with corporations and the state, in the context of globalization. The social consequences analysis of their distribution should be supplemented by the conditions analysis of their emergence and development.Materials and methods. The data of the Russian Public Opinion Research Center, research by the Institute of Psychology of the Russian Academy of Sciences, the National Research University Higher School of Economics, and others, are used in the work. The study results of social representations in modern psychology, sociology, and cultural anthropology are considered. The comparative historical method, structural-functional analysis, and typological approach are applied in the present work.Results. Typological concepts constructed by sociologists and a built-in hierarchy of problems significance provide social change interpretation schemes and turn into social representations. Spreading a kind of technocratic belief in a collective consciousness indicates the loss of heuristic potential concepts by a post-industrial, information society. This is especially true for the new version of society – the digital society. Sociological arsenal has ideal-typical constructions, whose cultural significance increases sharply. Civil society is a typological concept that focuses on the study of social forces and specific historical conditions which choose the direction of technological progress by supporting some and blocking other scientific and technological developments.Discussion. Technocracy is considered as an analytical perspective and a world view attributed to modern social representations. Changes in the structural-functional and content-morphological characteristics of social representations are studied. Digitalization is correlated with the typological concepts of the post-industrial and information society. Special attention is dedicated to the historical nature of sociological typological concepts.Conclusion. The article attempts to justify the design relevance of the typological concept "civil society" for understanding social alternatives and high technologies role in their implementation.